The Correlation of Hemostatic Parameters with the Development of Early Sepsis-Associated Encephalopathy. A Retrospective Observational Study - Scarlatescu Florin; Scarlatescu Ecaterina; Tomescu Dana Rodica; Bartos Daniela (The Journal of Critical Care Medicine)
Sepsis-associated encephalopathy (SAE) is one of the most common complications seen both in early and late stages of sepsis, with a wide spectrum of clinical manifestations ranging from mild neurological dysfunction to delirium and coma. The pathophysiology of SAE is still not completely understood, and the diagnosis can be challenging especially in early stages of sepsis and in patients with subtle symptoms.